Comparison of indirect and direct methods of distance sampling for estimating density of white‐tailed deer1. (29th December 2012) - Anderson, Charles W.; Nielsen, Clayton K.; Hester, Cyrus M.; Hubbard, Ryan D.; Stroud, Janice K.; Schauber, Eric M.
Abstract Although wildlife biologists need reliable estimates of white‐tailed deer (Odocoileus virginianus) density to facilitate management, few studies have examined distance sampling as a density estimation technique for this species. We compared direct (i.e., spotlighting from road transects) and indirect (i.e., counting pellets on randomly placed transects) distance‐sampling techniques for estimating deer densities in east‐central Illinois, southern Illinois, and northern Michigan (USA) during 2007–2008. Density estimates (95% CI) from indirect distance sampling for northern Michigan, east‐central Illinois, and southern Illinois were 6.1–12.7 deer/km2, 11.2–15.8 deer/km2, and 15.4 deer/km2, respectively. Density estimates from direct distance sampling for northern Michigan, east‐central Illinois, and southern Illinois were 18.3–25.2 deer/km2, 14.4–18.1 deer/km2, and 19.0 deer/km2, respectively. Although density estimates did not differ between techniques in east‐central Illinois and southern Illinois, density estimates derived by direct sampling were slightly higher than those derived by indirect sampling. Estimates of density from direct distance sampling were higher than indirect distance sampling in northern Michigan. The difference in estimates among study areas may be due to landscape‐specific differences in the behavioral response of deer to roads and the representativeness of road transects. In landscapes containing more agriculture, roads tend to be systematically distributed and forest edges are independent of road placement, which may explain why both distance‐sampling methods provided similar results in Illinois. However, in more forested landscapes such as Michigan, roads tend to follow streams and may provide forest edges that are relatively scarce on the landscape. Deer in forested landscapes may be attracted to roadsides, resulting in higher density estimates not indicative of surrounding forested areas. Therefore, use of road transects for direct distance sampling may be more applicable in non‐forested landscapes. © The Wildlife Society, 2012